Implementation of Tahfidz Curriculum Management in Tahfidz Qur'an Elementary School - Endang Sri Mulyani; Ida Rindaningsih (Indonesian Journal of Islamic Studies, 2021)
Curriculum management is an inseparable part of the education unit level curriculum (KTSP) and school-based management (SBM), curriculum implementation will run well if there is good management as well. This study aims to describe the implementation of the tahfidz quran curriculum management and what competencies are possessed by the outputs or graduates of SDTQ Al Aqsha Krian Sidoarjo. This research method uses descriptive qualitative with a phenomenological approach and analysis and interpretation techniques of Miles and Huberman model data, namely data reduction, data presentation, and conclusion drawing. The results of the study show that there is a link between the implementation of the tahfidz quran curriculum management with the results of SDTQ Al Aqsa graduates who have special competencies, namely having at least 2 (two) juz memorization of the Koran in graduating students.